Protected fat and variable level of protein in diets of crossbreed cows in early lactation - Alcy Heleno de Souza Júnior; Rogério de Paula Lana; César Roberto Viana Teixeira; Mateus Pies Gionbelli; Cristina Mattos Veloso; Luciana Navajas Rennó (Acta Scientiarum. Animal Sciences, 2016)
Current study evaluated the inclusion of protected fat and different levels of crude protein (CP) in the diet of crossbreed cows in early lactation. Twelve cows were distributed in a 4 x 4 factorial design, with four treatments (12 or 16% CP, with or without MEGALAC-E®). Statistical analyzes with ANOVA and Pearson’s linear correlation procedures were performed. Protected fat did not affect intake of dry matter (DM) and organic matter (OM) (p > 0.05). Increased CP raised consumption of CP and EE and decreased the non-fiber carbohydrates (NFC; p <0.05). Protected fat increased (p <0.05) the digestibility of DM, OM, CP and ashes in the lower protein content. CP increase raised the level of blood and urinary urea (p < 0.05). There was no difference (p > 0.05) on milk yield and composition due to protected fat or CP rates. Since the inclusion of protected fat and higher content of CP (16%) in the diet did not benefit the production and composition of milk in crossbreed cows, diets with 12% CP without the inclusion of protected fat are recommended.